79.2k views
2 votes
What is the solution to the system below? x + 5y = 4

x - 5y = -16

(6,-2)
(2,-6)
(-6,2)
(-2,6)​

User Riwalk
by
5.7k points

2 Answers

5 votes

Answer:

(-6, 2)

Explanation:

Put (-6, 2) into eq1 and eq2

1. (-6) +5(2)= -6 +10 =4

2.(-6) - 5(2)= -6-10 = -16

only one that works is (-6, 2)

User The Internet
by
6.5k points
2 votes

Answer:

(-6,2) third option is correct

Explanation:

x+5y=4 equation1

x-5y=-16 equation 2

by adding both equations we got

2x=-12

x=-6

now put x=-6 in any of the equation to get y...

-6+5y=4 equation 1

5y=4+6

5y=10

y=10/5

y=2

(-6,2)

User Scony
by
6.3k points